Increasing Students' Interest in Learning Islamic Education through the Project Based Learning Model at SMP Negeri 2 Sosopan - Hasibuan, Sofwan; Nasution, Nur Hamidah; Harahap, Immunirah (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning through the Project Based Learning Model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that through the Project Based Learning Model, it can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle it increased to 90.32%. Thus, through the Project Based Learning Model it can be used as an alternative to improve student learning outcomes in Islamic religious education learning.